ANALISIS PENGARUH JUSTICE (ADIL & JUJUR), ESTEEM (PELAYANAN TERBAIK) DAN FINISHING TOUCH (SENTUHAN AKHIR) TERHADAP LOYALITAS KONSUMEN PERAWATAN RAMBUT BARBERSHOP (BARBERBOX KELAPA GADING DAN BARBERBOX SENAYAN, JAKARTA): Analysis of the Effect of Justice, Esteem and Finishing Touch on Loyalty Consumer of Barberbox Kelapa Gading and Barberbox Senayan (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
This study aims to Analysis of the Effect of Justice, Esteem and Finishing Touch on Loyalty Consumer of Barberbox Kelapa Gading and Barberbox Senayan. The population is taken in this study is all consumers and customers that exist in Barberbox Kelapa Gading and Barberbox Senayan, Jakarta by taking asample of 99 respondents. The type of research used is descriptive and comparative.The technique of collecting data is done by filling the questionnaire. The analysistechnique used is validity test, reliability test, normality test, classic assumption test,and simultaneous test. The results shows that the loyalty consumer are influenced by Justice, Esteem and Finishing Touch at both Barberbox Kelapa Gading and Barberbox Senayan.